Pengembangan Instrumen Tes Diagnostik Five-Tier Multiple Choice untuk Mengidentifikasi Miskonsepsi Siswa pada Materi Kesetimbangan Kimia - Daniel Martua Sitorus; Makharany Dalimunthe (Jurnal Pendidikan Kimia FKIP Universitas Halu Oleo, 2024)
This research aims to report the results of identifying the level of misconceptions and the sources causing the misconceptions experienced by class XI IPA students at SMAN 17 Medan regarding the concept of chemical equilibrium. This research is descriptive research using the ADDIE development model. Data collection in this research used tests, interviews and questionnaires. The results of the wide-scale trial showed that the level of misconception of class The largest percentage of misconceptions is the concept of chemical equilibrium in industry at 29%. The lowest percentage of misconceptions experienced by students was understanding the concept of chemical equilibrium at 2%. The highest percentage of categories that cause misconceptions experienced by students is in the MC-PT category or misconceptions caused by individuals at 73% and the lowest category percentage was shown in the MC-B category or misconceptions obtained from books at 34%.